Neuroretorica dello "straniamento" (Comparatismi, 2025)
The theory of estrangement proposed by Russian formalist Viktor Shklovsky has found evidentiary support in Gestalt theory and partial opposition in the scientific community in recent years, especially in neurocognitivism. Psychologists and neuroscientists have highlighted not only how the right hemisphere of the human brain is specialized for processing the unknown before the left hemisphere intervenes to classify it, but also how novelty poses a potential danger where the hippocampus has no similar information stored. Thus, the brain’s fundamental function – predictive processing – can lead to prediction errors and disrupt the reward circuitry: even the so-called Stendhal syndrome must be reinterpreted today as a pernicious effect of the novum on the brain. This paper historicizes the concept of novelty starting from the early twentieth century and compares it to the current proliferation of serializations and adaptations, which act in the opposite way to Šklovskij’s defamiliarization, giving rise to repetition and the ever-the-same of mainstream aesthetics.
Keywords: Estrangement; Verfremdung; Novelty; Left hemisphere; Stendhal syndrome; Predictive processing